P1-S4.01 HIV/STD Coinfection in Arizona, 2000−2008: identifying opportunities for integrated surveillance and partner services. (10th July 2011) - Taylor, M; Winscott, M; Skinner, J; Ereth, R; Kenney, K; Bailey, R
Abstract : Background: Persons with HIV who acquire STDs such as chlamydia, gonorrhoea, and syphilis likely represent high-risk sources of HIV and STD transmission. Some state and local STD and HIV programs do not allow data sharing that would identify these individuals due to concerns with data security and confidentiality. Objective: To identify the number of STD cases that were known to have HIV prior to the time of the STD diagnosis. Methods: A probabilistic matching method was used to merge the HIV and STD surveillance databases at the Arizona Department of Health Services (ADHS). Partial matches were reviewed by hand to avoid misclassification. The person and diagnosis events from the HIV-STD merge were limited to gonorrhoea (GC), chlamydia (CT), primary and secondary syphilis (PS) and early latent syphilis (EL) diagnosed during 2000−2008. Persons diagnosed with GC, CT, PS or EL diagnosis were considered to be co-infected with HIV if the HIV diagnosis date was more than 60 days before the STD diagnosis date. Results: During 2000−2008, 1494 reported STD cases occurred among persons with previously diagnosed HIV. These cases included 14% (271/1960) of the PS, 9% (173/2043) of the EL, 2% (725/39 779) of the gonorrhoea, and 0.2% (325/171 010) of the CT cases reported to ADHS. HIV coinfection among syphilis cases was highest among males ages 35−39 (PS 25%, EL 19%), 40−44 (PS 27%, EL 24%) and 45−49 (PS 22%, EL 34%). Among male GC cases the age group with the greatest percentage of HIV coinfection was 40−44 at 9%. HIV coinfection among females reported with syphilis was highest in the age group 25−29 for PS (4%, 3 cases) and 40―44 for EL (2.4%, 2 cases). Among syphilis cases, white males had the greatest percentage of HIV co-infection (PS 31%, EL 32%). Similarly among GC and CT cases, white males had the highest percentages of HIV coinfection at 7% and 1% respectively. HIV coinfection was less than 1% among women in all age groups with CT and GC. A dramatic increase in the overall percent of HIV coinfection for syphilis was seen during the study period ranging from 0.5% in 2000 to 24% in 2008 for PS and 2% to 21% during the same time interval for EL. A similar but smaller increase in the overall percent of HIV co-infection for gonorrhoea was seen during the study period ranging from 0.7% in 2000 to 2.6% in 2008. Conclusion: Retrospective data integration identified many coinfected HIV/STD cases. Timely integrated HIV and STD surveillance would allow rapid identification of these persons who could be reached for more intensive counselling and partner services. Public STD and HIV programs should address comorbidity using methods that facilitate public health intervention.